Zum 80. Todestag von Dr. Walther Horn - Kutzscher, Christian (Contributions to Entomology = Beiträge zur Entomologie, 2019)
On the occasion of the 80th anniversary of his death on July 10, 2019, the life’s work of Dr. Walther Horn is honoured. Horn was director of the Deutsches Entomologisches Institut (German Entomological Institute) from 1909 to 1939. He was one of the most outstanding and best-known entomologists of his time. The focus is on his services to the sustained development of the Deutsches Entomologisches National-Museum (German Entomological National Museum), founded in 1886, which Horn developed into an internationally recognized research institute despite the difficult conditions of contemporary history. This institute continues to exist today as the Senckenberg Deutsches Entomologisches Institut, carrying out the main tasks envisaged by Horn, and still possesses many of the special features with which he endowed it. Horn’s achievements as an entomologist, museologist, science manager and humanist are highlighted. In honour of Horn, the Friends of the DEI (Förderverein des Deutschen Entomologischen Instituts e. V.) took over the care of his grave in Berlin-Lichterfelde in 2018.